Uterine Rupture with Hemoperitoneum in a Dog Managed by Ovariohysterectomy - Singh, Anmol; Singh, Khushpreet; Kaur, Dilraj; Singh, Narinder; Kumar, Ajeet (The Indian Journal of Animal Reproduction, 2026)
A potentially fatal consequence of canine dystocia is uterine rupture, which usually leads to peritonitis. A case of three year-old, mix breed female dog was presented that whelped one week earlier and suffered from severe abdominal disten sion. Radiograph demonstrated the presence of a single fetal skeleton within the abdominal cavity while ultrasonography revealed marked fluid accumulation. An emergency ovariohysterectomy was performed, and the dog recovered follow ing post-operative treatment. This procedure remains the treatment of choice in cases of prolonged dystocia associated with uterine rupture and hemoperitoneum.
Keywords: Canine; Hemoperitoneum; Ovariohysterectomy; Uterine rupture